Advanced cost allocation system - Idzni Santana (2010)
XYZ is a US-based pharmaceutical company, looking to improve its Cost Allocation process. This project is collaborated between three Business-IT undergraduates and the Finance Managers of XYZ Company to automate the Company‟s Cost Allocation process. The overall objective of this project is to improve the Cost Allocation system that XYZ Company is currently using so that Finance Managers can cope with data more effectively. The learning objective for the team in undertaking this project is to gain a firsthand experience of embarking on a real-life IT project development for an organization. This will enable the team to practice and hone both the technical and soft skills in handling IT projects. This is very important for Business-IT students as there is often a gap in the point of views between Business and IT side.